PERBEDAAN SEMANTIK ANTARA BAHASA INDONESIA DAN BAHASA MALAYSIA:Satu Kajian Awal Upaya Mengelak Kesalahpahaman dan Perbedaan Budaya Antara Bangsa Serumpun di Asia Tenggara - Promadi Promadi (Sosial Budaya, 2012)
In Indonesian and Bahasa Malaysia there are different meanings of the same word, though both languages are derived from the language of the Malay language. This can lead to misunderstandings between citizens of Malaysia and Indonesia in the communicating. The question that arises is how to form words meaning the difference between Indonesian and Bahasa Malaysia? This study is a qualitative research that produces descriptive data barupa words written or spoken about the observed behavior. The morphological differences were found present in the sound (phoneme), the form of words (morphemes), and meaning (semantics) of a word. This difference can be grouped to (a) the words have similar sounds and form words but have different meanings, such as sexy, slave, need, sex, hard, dead, may, demolished, and other marks, (b) different word forms of the word but have similar meanings, such as blades and spoons, direction and direction, Abun-Abun and wishful thinking, buy sides and shop, and they travel mengadar, crushed and terhempap, boxing and bertumbuk, ravaged and terjejas, and other (c ) words that sound different but have similar meanings, such as boys and men, bebola and balls, mouse, and rat-tikusan, mountain-range of mountains and mountains, once-scale and once in a while and others. To avoid misunderstandings in communication between the citizens of Malaysia and Indonesia to the competent authorities such as the Ministry of Education in this regard pergururan, or anyone who is interested, publish Dictionary Indonesian-Malaysia. It is expected that such a dictionary, any citizen of Indonesia and Malaysia will be assisted in communicating between countries.